The fossil flora of Great Britain or, figures and descriptions of the vegetable remains found in fossil state in this country - Lindley, John 1799-1865 (Cambridge library collection. Earth sciences, 2015)
Employed early on in his career by Sir Joseph Banks, the botanist John Lindley went on to conduct important research on the orchid family & also recommended that Kew Gardens should become a national botanical institution. This pioneering three-volume work of palaeobotany, first published between 1831 & 1837, catalogues almost 300 species of fossil plants from the Pleistocene to the Carboniferous period. The geologist & palaeontologist William Hutton, with whom Lindley collaborated, was responsible for collecting the fossil speciments from which the 230 plates were drawn. The first serious attempt at organising & interpreting the evidence of Britain's primeval plant life, this resource is notable also for its prefatory discussion of topics such as coal seams & prehistoric climate. Volume 2 opens with a preface on coal, followed by descriptions of some of the fossil plants found therein.